Numerical Prediction of Natural Convection Flow in the Presence of Weak Magnetic Prandtl Number and Strong Magnetic Field with Algebraic Decay in Mainstream Velocity (Advances in Applied Mathematics and Mechanics, 2018)
In present work, we investigate numerical simulation of steady natural convectionflow in the presence of weak magnetic Prandtl number and strong magneticfield by involving algebraic decay in mainstream velocity. Before passing to the numericalsimulation, we formulate the set of boundary layer equations with the inclusion ofthe effects of algebraic decay velocity, aligned magnetic field and buoyant body forcein the momentum equation. Later, finite difference method with primitive variableformulation is employed in the physical domain to compute the numerical solutionsof the flow field. Graphical results for the velocity, temperature and transverse componentof magnetic field as well as surface friction, rate of heat transfer and currentdensity are presented and discussed. It is pertinent to mention that the simulationis performed for different values of algebraic decay parameter $α$, Prandtl number $P_r$,magnetic Prandtl number $P_m$ and magnetic force parameter $S$.